Bis[(2,2-dimethylpropanoyloxy)methyl] {[2-(6-amino-9H-purin-9-yl)eth-oxy] methyl}phosphonate-succinic acid (2/1) - Jung, S.; Ha, J.-M.; Kim, I.W. (2012)
The title compound, C 20H 32N 5O 8P·0.5C 4H 6O 4, is composed of two 9-{2-[bis-(pivaloyloxymeth-oxy)phosphinylmeth-oxy]eth-yl}adenine, commonly known as adefovir dipivoxil (AD), mol-ecules linked to the carb-oxy-lic acid groups of succinic acid (SA). The asymmetric unit contains one mol-ecule of AD and half a mol-ecule of SA, which sits on an inversion center. Both adenine units in the two AD mol-ecules make AD-SA N - H？O and SA-AD O - H？N hydrogen bonds to SA. In addition, the inter-molecular AD-AD N - H？O - P hydrogen bond serves to stabilize the cocrystal. There is also a π-π stacking inter-action [inter-planar spacing 3.34 (19) ？] between adjacent inversion-related adenine groups.